2023
DOI: 10.1038/s41392-023-01342-6
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation in hematopoiesis and its implications in the targeted therapy of hematologic malignancies

Abstract: Hematologic malignancies are one of the most common cancers, and the incidence has been rising in recent decades. The clinical and molecular features of hematologic malignancies are highly heterogenous, and some hematologic malignancies are incurable, challenging the treatment, and prognosis of the patients. However, hematopoiesis and oncogenesis of hematologic malignancies are profoundly affected by epigenetic regulation. Studies have found that methylation-related mutations, abnormal methylation profiles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 776 publications
1
27
0
Order By: Relevance
“…HDACs regulate histone acetylation and act as transcriptional repressors, and their dysregulation is associated with hematological malignancies and lymphomas. 287 The study utilized blood-TPP to profile the targets of panobinostat, confirming its engagement with known HDACs in human whole blood and identifying an off-target, the zinc finger protein ZNF512. Furthermore, blood-CETSA was used to quantify and compare the dose-dependent engagement of HDAC2 by different HDAC inhibitors, including belinostat and romideps.…”
Section: Translational and Clinical Applications For Precision Medicinementioning
confidence: 92%
“…HDACs regulate histone acetylation and act as transcriptional repressors, and their dysregulation is associated with hematological malignancies and lymphomas. 287 The study utilized blood-TPP to profile the targets of panobinostat, confirming its engagement with known HDACs in human whole blood and identifying an off-target, the zinc finger protein ZNF512. Furthermore, blood-CETSA was used to quantify and compare the dose-dependent engagement of HDAC2 by different HDAC inhibitors, including belinostat and romideps.…”
Section: Translational and Clinical Applications For Precision Medicinementioning
confidence: 92%
“…Recently, many studies have demonstrated that lncRNAs are involved in different malignancies, including lymphomas. In haematologic malignancies, lncRNAs may affect cell proliferation, invasion and resistance to treatment through different pathways 8 …”
Section: Introductionmentioning
confidence: 99%
“…In haematologic malignancies, lncRNAs may affect cell proliferation, invasion and resistance to treatment through different pathways. 8 Furthermore, studies have shown changes in lncRNA expression in different stages of the maturation of lymphocytes. 9 Understanding the lncRNA mechanism of action provides more information about lymphoma's pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Its absence severely impacts immune system function and leads to developmental defects in HSCs and impaired macrophage proliferation (Dey et al, 2019). In this issue, Yang et al (2023) extensively investigate various progenitor cell populations and their lineage commitment to myeloid cells in the absence of BRD4. The conditional deletion of BRD4 in the hematopoietic system of 6-8-week-old mice results in lethality and a substant increase in HPCs that possess, however, restricted colony-forming capacity and selfrenewal activity.…”
mentioning
confidence: 99%
“…In apparent contrast, in macrophages in the absence of BRD4, ligand-induced NF-jB binding is not reduced; instead, it increases, leading to significant inflammatory responses in BRD4 KO macrophages (Dey et al, 2019). However, the exact mechanism responsible for this unexpected finding remained unclear until the work of Yang et al (2023), which sheds light on this contrasting observation.…”
mentioning
confidence: 99%